Comparison of patient survival and technique survival between continuous ambulatory peritoneal dialysis and automated peritoneal dialysis. Issue 6 (November 2020) - Wang, I-Kuan; Yu, Tung-Min; Yen, Tzung-Hai; Lin, Shih-Yi; Chang, Chia-Ling; Lai, Ping-Chin; Li, Chi-Yuan; Sung, Fung-Chang
Background: This retrospective cohort study compared patient survival and technique survival between patients on continuous ambulatory peritoneal dialysis (CAPD) and automated peritoneal dialysis (APD) using recent data at a single tertiary medical center in Taiwan. Methods: From medical records, we identified incident 459 CAPD patients and 266 APD patients on dialysis for at least 90 days and aged more than 18 years to estimate mortality and technique failure rates, and related hazard ratio (HR) and 95% confidence interval (CI) from 2007 to 2018. Results: There were more women (52.3%) in the CAPD group, whereas patients in the APD group were younger. Compared to CAPD patients, APD patients had a lower mortality rate (2.83 vs. 5.79 per 100 person-years) with an adjusted HR of 0.69 (95% CI = 0.47–1.02), and a lower technique failure rate (9.70 vs. 17.52 per 100 person-years) with an adjusted HR of 0.65 (95% CI = 0.51–0.83). Further subgroup analyses revealed that, compared to CAPD, APD was associated with a significant lower risk of technique failure in male patients, patients aged 50–65 years, diabetic patients, patients without cardiovascular disease (CVD), patients with higher peritoneal permeability, or patients initiating PD in an earlier era. Conclusions: The mortality risk was not significant between CAPD and APD patients. APD is associated with a lower risk of technique failure than CAPD, particularly for male patients, and patients aged 50–65 years, with diabetes, without CVD, with high or high average peritoneal permeability, or initiating PD in an earlier era.